2015
DOI: 10.1080/15700763.2014.997935
|View full text |Cite
|
Sign up to set email alerts
|

School Process and Teacher Job Satisfaction at Alternative Schools: A Multilevel Study Using SASS 2007–08 Data

Abstract: This study examined the associations between public alternative schools' teacher job satisfaction and school processes. Based on a multilevel analysis of the national School and StaffingSurvey 2007-08 data, we found that among the seven school processes, public alternative schools' administrative support, staff collegiality, career and working condition, and positive student behavior had positive associations with teacher job satisfaction. More importantly, we noticed that higher level factors (e.g., administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…This means that policies and practices that support increased teacher involvement in decision-making related to school management may help raise teacher job satisfaction and professional commitment—key organizational outcomes for schools. This finding is consistent with a large body of prior research on teacher job satisfaction (Bogler and Nir, 2010; Carolyn and William, 2005; Kelly, 2004; Scott-Ladd et al, 2006; Shen et al, 2012; Stockard and Lehman, 2004; Wright et al, 2018; Xia et al, 2015) and teacher professional commitment (Bogler, 2005; Liu, 2007; Riehl and Sipple, 1996; Scott-Ladd et al, 2006; Somech and Bogler, 2002). Indeed, researchers note that when teachers are highly involved in decision-making, they feel a greater sense of ownership and commitment to their profession and schools, which in turn leads to greater job satisfaction and retention (Brezicha et al, 2020; Ingersoll, 2003; Leech and Fulton, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This means that policies and practices that support increased teacher involvement in decision-making related to school management may help raise teacher job satisfaction and professional commitment—key organizational outcomes for schools. This finding is consistent with a large body of prior research on teacher job satisfaction (Bogler and Nir, 2010; Carolyn and William, 2005; Kelly, 2004; Scott-Ladd et al, 2006; Shen et al, 2012; Stockard and Lehman, 2004; Wright et al, 2018; Xia et al, 2015) and teacher professional commitment (Bogler, 2005; Liu, 2007; Riehl and Sipple, 1996; Scott-Ladd et al, 2006; Somech and Bogler, 2002). Indeed, researchers note that when teachers are highly involved in decision-making, they feel a greater sense of ownership and commitment to their profession and schools, which in turn leads to greater job satisfaction and retention (Brezicha et al, 2020; Ingersoll, 2003; Leech and Fulton, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Teacher job satisfaction is associated with individual involvement and power in various types of school decisions (Brezicha et al, 2020). Many studies show that teacher job satisfaction is positively related to the extent of classroom control and influence in school decision-making (Bogler and Nir, 2010; Carolyn and William 2005; Kelly, 2004; Scott-Ladd et al, 2006; Shen et al, 2012; Stockard and Lehman, 2004; Wright et al, 2018; Xia et al, 2015). Teacher participation in school decision-making depends on preferences, interests, expertise, and demand- or support-generating processes.…”
Section: Theoretical Background and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A national empirical study in the USA reported that, for alternative schools, school completion was significantly correlated with positive teacher qualities (Xia, Izumi & Gao, 2015).…”
Section: The Emotional Work Of Teachers In Alternative Schoolsmentioning
confidence: 99%
“…The supportive environments which cultivate positive staff-student relationships at alternative schools are, thus, often considered to be a barometer of the quality of these schools (Xia et al, 2015;Mills & McGregor, 2010). The positive emotional connections often developed between the staff and young people at these schools are critical to their effectiveness (McGregor & Mills, 2012;te Riele, 2012) and can literally be 'life changing' for students (Australian Industry Group & Dusseldorp Skills Forum, 2007, p. 35).…”
Section: The Emotional Work Of Teachers In Alternative Schoolsmentioning
confidence: 99%